Use of nicotine products — a cross-sectional survey of adolescents in Poland - Piotr Korczyński; Stanisław Surma; Agnieszka Jankowska-Zduńczyk; Sebastian Szmit; Piotr Wierzbiński; Janusz Sytnik-Czetwertyński; Krzysztof J. Filipiak (Folia Cardiologica)
INTRODUCTION: Cigarette smoking has been a significant health problem in the world for decades. Currently, new forms of smoking are becoming increasingly popular — e-cigarettes and tobacco heating systems (HnB, heat-not-burn), whose impact on the human body is not indifferent. Young people, including teenagers, are particularly keen to use these products, which has serious consequences for their health. MATERIAL AND METHODS: The study used an original survey questionnaire containing single- and multiple-choice questions. The study group included a representative group of 1000 adolescents aged 16–17 years from all over Poland, both from small towns and large cities. RESULTS: Most importantly, 56% of respondents had already initiated nicotine use — they had already tried a nicotine-providing product. Of these, 75% had made their first attempt at using a nicotine product by the age of 15 years. Interestingly, nearly 58% of respondents initiated their use of nicotine-providing products with an e-cigarette, while nearly 41% started using a traditional cigarette. In terms of motivation, nearly 68% of respondents initiated nicotine providing products because they were “curious about the taste of this product”, while the second important reason (50%) was “the desire to try something new”. It is worth emphasizing that 31% of respondents used nicotine products every day after initiation. Of the respondents currently using nicotine products, 78% use e-cigarettes, while nearly 24% smoke traditional cigarettes, and over 7% use HnB systems. Over 80% of respondents currently use nicotine products because of their taste (87% choose fruit/sweet or dessert flavors). A 69% of respondents purchase nicotine products from shops or kiosks. Notably, over 23% of respondents asked an adult to purchase nicotine products for them. Interestingly, 86% of respondents do not feel addicted to nicotine products, although 95% claim to know the health risks associated with using this type of product. CONCLUSIONS: Smoking cigarettes, especially flavored e-cigarettes, is a serious problem among Polish 16- and 17-year-olds. Given the high addictive potential of these products, urgent legal regulations prohibiting the sale of these products to minors are expected. Social awareness of the harmfulness of new forms of smoking should also be increased.